PERAN POLRESTA KOTA JAYAPURA DALAM IMPLEMENTASI PERMENHUB NOMOR 45 TAHUN 2020 DAN KESADARAN MASYARAKAT DALAM PENGGUNAAN SEPEDA LISTRIK DI JALAN RAYA - mukti, margo; Safiudin; zulfadli (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
Electric bikes are one of those included in the Regulation of the Minister of Transportation (Permenhub) Number 45 of 2020 concerning vehicles using electric motor drives. The fist research problem in this study is to examine the role of the Jayapura City Resort Police (Polresta) in implementing Permenhub number 45 of 2020 and the awareness of the people of Jayapura City towards the use of electric bikes on the higway. In accordance with article 5 paragraph (1) of the minister of Transportation, it is explained that electric bikes are in special lanes or certain areas. The use of the electric bikes on higway can be very dangerous for users and other riders. The result of this in Permenhub number 45 of 2020, it has not been included in the regulations of the Jayapura City Police in the Satlantas section, this is why the Police have not yet given administrative sanctions reprimands against violators. The preventive efforts made by the Jayapura City Police are in the form of giving an appeal not to use electric bikes on the higway which is uploaded on social media. The second research result is that the awarenes of the law of the people of Jayapura City towards the use electric bikes is actually quite high, because they have known about this prohibition from dealers and social media, but compliance with the law is still quite low, the factor that affects this violation is the lack of availability of supporting facilities and facilities as stated in the Minister of Thansportation Regulation (Permenhub) Number 45 of 2020, and the legal status is less certain so that the legal force is less binding.